Cancer survivorship at heart: a multidisciplinary cardio-oncology roadmap for healthcare professionals - Bisceglia, Irma; Canale, Maria Laura; Silvestris, Nicola; Gallucci, Giuseppina; Camerini, Andrea; Inno, Alessandro; Camilli, Massimiliano; Turazza, Fabio Maria; Russo, Giulia; Paccone, Andrea; Mistrulli, Raffaella; De Luca, Leonardo; et al. (Frontiers in Cardiovascular Medicine, 2023)
In cancer, a patient is considered a survivor from the time of initial diagnosis until the end of life. With improvements in early diagnosis and treatment, the number of cancer survivors (CS) has grown considerably and includes: 1) Patients cured and free from cancer who may be at risk of late-onset cancer therapy-related cardiovascular toxicity (CTR-CVT); 2) Patients with long-term control of not-curable cancers in whom CTR-CVT may need to be addressed. This paper highlights the importance of the cancer care continuum, of a patient-centered approach and of a prevention-oriented policy. The ultimate goal is a personalized care of CS, achievable only through a multidisciplinary-guided survivorship care plan, one that replaces the fragmented management of current healthcare systems. Collaboration between oncologists and cardiologists is the pillar of a framework in which primary care providers and other specialists must be engaged and in which familial, social and environmental factors are also taken into account.